• Упрoстите выражение:
    (2x^0,75 + 3x^0,25)^2 - 4x^0,5 × (x+2,25)

Ответы 1

  • (2x^0,75 + 3x^0,25)^2 - 4x^0,5 × (x+2,25) = 12x

    (2x^{0,75}+3x^{0,25})^2-4x^{0,5}*(x+2,25)=

    =(4x^{1,5}+2*2x^{0,75}*3x^{0,25}+9x^{0,5})-4x^{0,5}*(x+2,25)=(4x^{1,5}+12x^1+9x^{0,5})-4x^{0,5}*(x+2,25)=(4x^{1,5}+12x+9x^{0,5})-4x^{0,5+1}-2,25*4x^{0,5}=4x^{1,5}+12x+9x^{0,5}-4x^{1,5}-9x^{0,5}=12x

  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years